The influence of influencer marketing, and hedonic motivation on purchasing decisions on the Tiktok application in Padang City with fear of missing out (FoMo) as a mediating variable. - Effita Suri, Nadia; Septrizola, Whyosi (Marketing Management Studies, 2024)
This study aims to analyze the effect of influencer marketing and hedonic motivation on consumer purchasing decisions on the TikTok application in Padang City with Fearof Missing Out (FoMo) as the Mediating Variable. The number of samples in this study were 210 respondents. The research data was collected through distributing questionnaires online and the analysis technique used in this study was the Structural Equation Modeling (SEM) analysis technique with PLS 4.0 software. The results of this study indicate (1) Influencer marketing has a significant effect on fear of missing out (FoMo) (2) Fear of missing out (FoMo) has a significant positive effect on consumer purchasing decisions (3) Influencer Marketing has a significant positive effect on consumer purchasing decisions (4) Hedonic motivation has a significant effect on consumer purchasing decisions (5) Influencer marketing has a negative and significant effect on purchasing decisions with fear of missing out (FoMo) as mediation.